(untitled) (Faridpur Medical College Journal, 2013)
Methamphetamine dependence is a serious worldwide public health problem with major medical, psychiatric, socioeconomic & legal consequences. Various neuronal mechanisms implicated in methamphetamine dependence have been suggested. Drugs of abuse are of two types: natural drugs and synthetic psychotropic substances. The former includes opium, cocaine and cannabis. The latter includes pethidine, barbiturates, tranquillizers, amphetamines. There has been increasing incidence of addiction to certain drugs amongst young people in our country. Our patient is a student of private university of 24 year old male with a history of YABA addiction for 4 years. Without having it he can’t do anything. If he cannot take it, peevish temperament occurs. He collects drugs from the local spots or particular person. This condition is very much dangerous to the individual and socio-economic condition of country. DOI: http://dx.doi.org/10.3329/fmcj.v7i2.13527 Faridpur Med. Coll. J. 2012;7(2):102-104